Douglas Bennett Cockerell papers - Cockerell, Douglas
Chiefly letters written by Cockerell to his brother, Theodore D.A. Cockerell, in the United States, concerning family and social conditions in England during World War II. Includes some letters from his wife, Marion Cockerell, drafts of three articles he wrote on the war and its effect on the homemaker, and two printed articles by Theodore D.A. Cockerell.
Typewritten transcripts produced from originals in the hands of Theodore D.A. Cockerell.
English bookbinder. Full name: Douglas Bennett Cockerell. Born 1870; died 1945.
Collection material in English.
Keywords: Cockerell, Marion -- Correspondence; Cockerell, Theodore D. A. -- 1866-1948.; Cockerell, Theodore D. A. -- 1866-1948 -- Correspondence; Housewives -- Great Britain; World War, 1939-1945 -- Great Britain; Great Britain -- Social life and customs; Bookbinders